Factors associated with poor sleep among a sample of community-based New Zealand older adults : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology, School of Psychology, Massey University, New Zealand - Henry, Jamie Rose (Massey University, 2023)
Background: Sleep is well documented as a vital element in healthy ageing. However, to date, research concerning the sleep of older New Zealanders has used single or short-form items, limiting the estimations of sleep problems and the factors associated with them. The Ageing Well through Eating, Sleeping, Socialising and Mobility (AWESSoM) programme includes comprehensive measurements of sleep. This study aimed to describe the sleep status of community-dwelling older adults in New Zealand (NZ), and explore the factors associated with problematic sleep defined by both poor sleep quality and increased risk of obstructive sleep apnoea (OSA). Methods: A sample of 88 older adults (aged 63-93 years, 70.5% female) completed a survey as a component of the AWESSoM study. Problematic sleep was firstly defined as poor sleep quality using the Pittsburgh Sleep Quality Index (PSQI). Then increased risk for OSA was defined using the STOP-Bang questionnaire. Likelihood of being defined as a problem sleeper was explored with regards to demographic status, physical and mental health status (Short-Form Health Survey [SF-12]), cognitive functioning (Rowlands Universal Dementia Assessment Scale [RUDAS]) and activities of daily living (Nottingham Extended Activities of Daily Living [NEADL]) using chi-square and Mann-Whitney U tests followed by binary logistic regression. Results: Over half of the sample (55.7%) were defined as having poor sleep quality and 51% were defined as having a moderate to high risk of OSA. Female gender (OR = 4.098, 95% CI [1.18, 14.08]) and reduced cognitive functioning (OR = 0.736, 95% CI [0.566, 0.957]) were independently related to belonging to the poor sleep quality group. Male gender (OR = 92.34, 95% CI [9.607, 887.719]), younger age (OR = 0.866, 95% CI [0.777, 0.996]), and increased comorbid health conditions (OR = 1.503, 95% bCI [1.085, 2.083]) were independently associated with having medium-to-high risk of OSA. Conclusion: This thesis contributes to the growing body of evidence that suggests poor sleep is prevalent within the older adult population and that the factors associated with sleep are multifactorial and vary with the type of sleep disturbance. Findings will contribute to informing future interventions that promote sleep health, enabling older adults to age well and stay independent for longer.
Keywords: Sleep health; poor sleep; older adults; New Zealand; quantitative; 520304 Health psychology